Comparison of quality of life of older adults living in foster families versus nursing homes. Results from the KASA studies - Denis Boucaud-Maitre; Nadine Simo; Roxane Villeneuve; Michel Bonnet; Moustapha Dramé; Maturin Tabué-Teguo (Elsevier, 2024)
Objectives: Professional foster families for dependent older adults could be an alternative to nursing homes. Engagement in the family life and close contact with a single reference person could enhance their quality of life (QOL). This study aimed to compare the Health-Related Quality of Life (HrQOL) and subjective QOL among older adults living in foster families versus those in nursing homes. Design: Cross-sectional analysis from twin studies conducted in foster families (the KASAF study) and nursing homes (the KASEHPAD study). Setting and participants: Older adults (aged 60 years or older) in French Caribbean Islands living in foster families or nursing homes. Measurements: HrQOL was measured using the EuroQol-five dimensions (EQ5D-3L) and QOL was assessed using a Visual Analog Scale (QOL-VAS). For older adults unable to complete these scales, proxy EQ-5D-3L assessments were conducted by paramedical staff or foster caregivers. Results: A total of 439 older adults, with 107 in foster families and 332 in nursing homes were included. Participants living in foster families were less often male, had less often hypertension, were more dependent or physical impaired and had lower score of cognition. In multivariate analyses, factors associated with low self-reported HRQoL (n = 240) were Mini Mental State Examination (MMSE) score (β: −0.011; p = 0.003) and Activities of Daily Living (ADL) score (β: 0.014; p < 0.001). A lower QOL-VAS score (n = 150) was associated with living in a nursing home compared to living in a foster family (β: −19.48 points; p < 0.001) and with the ADL score (2.94 points; p = 0.019). In older adults with major cognitive disorders, the only factor associated with low proxy EQ-5D proxy index score (n = 136) was dependency (β: 0.167; p < 0.001). Conclusion: HrQOL was similar between older adults living in nursing homes and foster families. Additionally, older adults reported a better subjective quality of life when residing in foster families. These findings suggest that the foster family model may meet the social and environmental needs of dependent older adults for whom nursing homes are not suitable.